A novel insertional allele of the CG18135 gene is associated with severe mutant phenotypes in Drosophila melanogaster - Ratiu, Attila Cristian; Ionascu, Adrian; Ecovoiu, Alexandru Al. (Frontiers in Genetics, 2024)
Drosophila melanogaster has been at the forefront of genetic studies and biochemical modelling for over a century. Yet, the functions of many genes are still unknown mainly because no phenotypic data are available. Herein, we present first evidence data regarding the particular molecular and other quantifiable phenotypes, such as viability and anatomical anomalies, induced by a novel PlacW insertional mutant allele of CG18135 gene. So far, the CG18135 functions have only been theorized based on electronic annotation and presumptive associations inferred upon high-throughput proteomics or RNA sequencing experiments. The descendants of individuals harboring the CG18135 PlacWCG18135 allele were scored in order to assess mutant embryos, larvae and pupae viability versus Canton Special. Our results revealed that the homozygous CG18135 PlacWCG18135 /CG18135 PlacWCG18135 genotype determines significant lethality both at the inception of larval stage and during pupal development. The very Ffew imago escapers that either breach or fully exit the puparium and even more rarely fully exit from it exhibit specific eye depigmentation, wing abnormal unfolding, and strong locomotor impairment with apparent spasmodic legs movements. and Ttheir maximum lifespan is shorter than two days. When uUsing the quantitative Real-Time PCR (qRT-PCR) method to confirmwe found that CG18135 is indeed upregulated in males, but compared to females an unexpected gene upregulation was also detected in heterozygous mutants comparative to wild-type flies, probably because of regulatory perturbations induced by the PlacW transposon. Our work provides the first phenotypic evidence for the essential role of CG18135, a scenario in accordance with the putative role of this gene in the carbohydrate binding processes.